Preparation and electrochemical capacitive performance of phenolated calcium lignosulfonate-based phenol formaldehyde resin porous carbon. Issue 9 (6th March 2018) - Dai, Junxiu; Ma, Yanli; Ren, Shixue; Fang, Guizhen
Abstract: Abstract : Lignin-based phenol formaldehyde resin was synthesized using phenolated calcium lignosulfonate, and porous carbon with good wettability was prepared after carbonization and potassium hydroxide (KOH) activation. The results indicated that when the KOH to the carbonized sample mass ratio was 6:1, the prepared carbon had a rich porous structure and higher surface area, with a specific surface area of 1320.13 m 2 /g. Furthermore, the porous carbon exhibited a maximum specific capacitance of 204.88 F/g at a current density of 0.5 A/g in the potential range −1.0 to 0 V in a 6 M KOH solution and a low equivalent series resistance of 0.64 Ω. The phenolated calcium lignosulfonate-based phenol formaldehyde resin porous carbon demonstrated a favorable electric double-layer performance.